2013
DOI: 10.1159/000354453
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Histone Deacetylases Potentiates BMP9-Induced Osteogenic Signaling in Mouse Mesenchymal Stem Cells

Abstract: Background/Aims: We have demonstrated that bone morphogenetic protein 9 (BMP9) is one of the most potent BMPs in regulating osteoblast differentiation of mesenchymal stem cells (MSCs) although the molecular mechanism underlying BMP9-induced osteogenesis remains to be fully elucidated. It is known that epigenetic regulations play an important role in regulating the stem cell potency and lineage commitment. Here, we investigate if the inhibition of histone deacetylases (Hdacs) affects BMP9-induced osteogenic dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Furthermore, histone deacetylases were found to play a critical role in BMP9-mediated osteogenic signaling in mouse mesenchymal stem cells [11]. In the present study, the in vitro development of parthenogenetic embryos was enhanced with VPA treatment.…”
Section: Discussionsupporting
confidence: 49%
“…Furthermore, histone deacetylases were found to play a critical role in BMP9-mediated osteogenic signaling in mouse mesenchymal stem cells [11]. In the present study, the in vitro development of parthenogenetic embryos was enhanced with VPA treatment.…”
Section: Discussionsupporting
confidence: 49%
“…Since histone acetylation contributes to osteogenic differentiation of MSCs 19 , we profiled expression of 15 histone acetylases in H-PDLSCs and P-PDLSCs. The results showed that in comparison to H-PDLSCs, KAT2A, MOZ, MORF, EP300 and HAT1 were suppressed in P-PDLSCs as assayed by qRT-PCR analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In order to precisely observe the effects of HIF-1α on the BMP2-induced progression of chondrogenesis and endochondral ossification, a fetal limb culture was performed. Fetal limb cultures can mimic the progression of chondrogenesis and endochondral ossification in vitro [38,51,52]. The results revealed that HIF-1α and BMP2 acted synergistically inin expanding the proliferating chondrocyte zone and inhibiting the BMP2-induced chondrocyte hypertrophy and endochondral ossification zone.…”
Section: Disscussionmentioning
confidence: 99%